ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA PADA PEMBANGUNAN POLIKLINIK FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA TAHAP KE II - alawau, Boadicea Evalin; Leuhery, Lenora; Titaley, Henriette Dorothy (Journal Agregate, 2025)
The purpose of implementing occupational safety and health is to maintain the safety and health of the work environment and to protect. This study employs a data collection method by distributing questionnaires to employees on construction projects. The data analysis in this study involves respondent analysis (Validity Test, Reliability Test) and regression analysis (t-test, Determination Test). The analysis in this study is Quantitative using the SPSS Version 20 program. Based on the tests conducted, the magnitude of K3 application in the Construction of the Polyclinic at the Faculty of Medicine, Pattimura University, is 69.9%, indicating that the application of K3 in this project is quite effective. Among the independent variables, the most dominant variable can be seen from the results of the highest standardized coefficient beta value, namely in the Worker Awareness variable (X3) of (0.813 or 81.3%).